2022
DOI: 10.3389/fmicb.2022.1092854
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing bacterial communities in Phragmites australis rhizosphere and non-rhizosphere sediments under pressure of antibiotics in a shallow lake

Abstract: IntroductionAntibiotics are ubiquitous pollutants and widely found in aquatic ecosystems, which of rhizosphere sediment and rhizosphere bacterial communities had certain correlation. However, the response of bacterial communities in Phragmites australis rhizosphere and non-rhizosphere sediments to antibiotics stress is still poorly understood.MethodsTo address this knowledge gap, the samples of rhizosphere (R) and non-rhizosphere (NR) sediments of P. australis were collected to investigate the differences of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, there was no significant difference in the bacterial community structure in pore water between the wild and cultivated P. australis regions under the same antibiotics stress. The possible explanation was no significant difference in the total antibiotics in pore water between both regions ( Zhang et al, 2022a , b ), What is more, the similar bacterial community in sediments between both regions might be explained by the fact that the two P. australis regions were connected by inflow rivers, and the bacterial communities may coalesced between pore water and sediments ( Ren et al, 2017 ; Gao et al, 2021 ). It is different from the previous research that the bacterial community in pore water in different types of wetlands can be distinguished ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, there was no significant difference in the bacterial community structure in pore water between the wild and cultivated P. australis regions under the same antibiotics stress. The possible explanation was no significant difference in the total antibiotics in pore water between both regions ( Zhang et al, 2022a , b ), What is more, the similar bacterial community in sediments between both regions might be explained by the fact that the two P. australis regions were connected by inflow rivers, and the bacterial communities may coalesced between pore water and sediments ( Ren et al, 2017 ; Gao et al, 2021 ). It is different from the previous research that the bacterial community in pore water in different types of wetlands can be distinguished ( Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicological effects ( Välitalo et al, 2017 ) and the pressure selection ( Zhu et al, 2019 ; Sun et al, 2021 ) of antibiotics on bacterial communities ultimately change the bacteria populations, which could affect the migration of bacterial communities and the balance of the ecosystem. However, the distribution of antibiotics in aquatic environments was different, such as in pore water and sediments ( Xu et al, 2014 ; Zhang et al, 2022a , b ). Keshri et al (2018) found that pore water and sediment share 6.7–20.3% of operational taxonomic units (OTUs), which indicated a link between sediment bacterial communities and pore water bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations